The impact of the Basel III liquidity coverage ratio on macroeconomic stability: An agent-based approach - Boyao Li (Kiel Institute for the World Economy (IfW), 2017)
Commercial banks across the world have been implementing the Basel III accord, which is the most important international response to the 2007-2008 financial crisis. Particularly, the liquidity coverage ratio (LCR) introduced by the Basel III accord is the first global standard for banking liquidity management. Does this requirement work? And what macroeconomic effects does it produce? In order to address such crucial issues, the author develops a stock-flow consistent (SFC)/agent-based computational economic (ACE) model. As he knows, there is a real danger that the requirement restricts the availability of bank credit and hence reducing economic activity. However, in comparison to the prior works, the author finds that the externality is presented as a positive self-reinforcing feedback process, which causes the macroeconomic conditions to spiral downwards. This dynamic feedback process that hardly can be revealed by the current macroeconomic models based on equilibrium analyses. The results also shed some light on the fact that credit creation substantially affects economic activity and macroeconomic stability, as the fundamental reason leading to the results. Therefore, the bank as the driver of credit creation is crucial in an economy, and meanwhile bank regulations have great potential impacts on entire economy rather than only in the bank sector itself.
Keywords: E27; E44; E51; E32; G01; G28; 330; credit creation; liquidity coverage ratio; bank regulation; economic stability; agentbased macroeconomics; stock-flow consistency; business cycle; crisis